Augmented reality-assisted training with selected Tai-Chi movements improves balance control and increases lower limb muscle strength in older adults: A prospective randomized trial - Po-Jung Chen; I-Wen Penn; Shun-Hwa Wei; Long-Ren Chuang; Wen-Hsu Sung (Elsevier, 2020)
Background/Objective: Tai-Chi benefits older adults by enhancing balance control and increasing the muscle strength of the lower limbs. However, a complete set of traditional Tai-Chi exercises is sometimes too difficult for beginners. We investigated whether practicing augmented reality-assisted training with selected Tai-Chi movements tailored to the practitioner's ability (selected Tai-Chi, or sTC) is as effective as performing a complete set of Tai-Chi sequences (complete traditional Tai-Chi, or tTC). Methods: In this prospective randomized trial carried out in the Beitou District of Taipei City, Taiwan, community-dwelling adults aged ≥65 and without any debilitating diseases (n = 28) were included. Participants were randomly assigned to the sTC group (n = 14) or the tTC group (n = 14). Participants in the sTC group practiced selected Tai-Chi movements using the augmented reality Tai-Chi training system. Participants of the tTC group were asked to complete the 24-form Yang-style Tai-Chi following the instructions of Tai-Chi masters. Each training session lasted 30 min, with 3 sessions per week for 8 weeks. Pre- and post-intervention evaluations included functional balance tests, comprising the Berg Balance Scale (BBS), Timed Up and Go test (TUG), and Functional Reach Test (FRT), as well as muscle strength measurements of the lower extremities. Results: Pre-intervention evaluations showed significant differences in FRT (p = 0.034) and left hip abductor muscle strength (p = 0.046) between the sTC and tTC groups. After 8 weeks of training, the BBS, TUG, and FRT scores in the sTC group showed significant improvement overall. Although all three functional balance test scores improved in the tTC group, only the improvement in BBS was statistically significant (p = 0.001). After 8 weeks, all muscle strength measurements increased by an average of 3.1 ± 1.0 kgw in the sTC group and 1.6 ± 0.8 kgw in the tTC group. Conclusions: The augmented reality-assisted training with selected Tai-Chi movements, designed based on objective measurements of the practitioner's capability, improved balance control and muscle strength of lower limbs at least as effectively as the complete sequence of traditional Tai-Chi exercises. Trial registration: This study was approved by the Institutional Review Board of National Yang-Ming University (IRB number: 1000087). Written informed consent was obtained from all participants.